MENINGKATKAN KREATIVITAS GURU DALAM MENGAJAR PADA MASA PANDEMI COVID-19 MELALUI METODE PEMBERIAN TUGAS DI SLB NEGERI PEMBINA PEKANBARU - Yasni Yasni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Based on the results of pre-research observations conducted by researchers on Monday at Pembina State SLB Pekanbaru, problems were found, namely: There are still teachers who have not been able to apply online learning at home due to limitations in technology. There are still many teachers who apply the learning model with many assignments without paying attention to the situation and conditions during this covid-19 outbreak. Learning is only monotonous and by using creative learning models that are fun and not boring for children, children's character and creativity must continue to be fostered. Giving too much material and tiring children makes children lose their appetite for learning. The type of research is school action research with a sample of 34 teachers at SLB Pembina Pekanbaru. Based on the results of the analysis and discussion, it can be concluded that the creativity of teachers in teaching at SLB Pembina Pekanbaru can be increased through the assignment method. Under these conditions, the level of teacher acceptance increases. Comparison of aspects of teacher creativity in teaching through the assignment method in cycle I and II increased from 58.8% and cycle II to 75.1%.